Implications for conservation and game management of the roadkill levels of the endemic Iberian hare (Lepus granatensis) - Duarte, Jesús; Romero-Pacheco, David; Rubio, Pablo J; Farfán-Aguilar, Miguel Ángel; Fa, Julia E. (Nature Publishing Group, 2021)
The Iberian hare (Lepus granatensis) is an important small game species endemic to the Iberian Peninsula for which the incidence of roadkill is unknown. We surveyed Iberian hare–vehicle accidents on road networks in southern Spain, focusing on roads that mainly run through favorable habitats for this species: Mediterranean landscapes with plots of arable crops, olive groves, and vineyards. We recorded roadkills over a 5-month period, estimated hare accident densities on roads, and compared these numbers to hare hunting yields in adjoining hunting estates. We also analyzed the spatial patterns of and potential factors influencing hare roadkills. We detected the existence of black spots for hare roadkills in areas with high landscape heterogeneity that also included embankments and nearby crossroads and had high traffic intensity. Hare roadkill levels ranged from 5 to 25% of the annual harvest of hares killed on neighboring hunting estates. We suggest that road collisions should be considered in Iberian hare conservation in addition to hunting, since they may represent an additive source of mortality. Game managers should address the issue of hare roadkill in harvest planning to compensate for hare accidents, adjusting hunting quotas to account for this unnatural source of mortality. Our results suggest future directions for applied research in road ecology, including further work on demographic compensation and roadkill mitigation.
Keywords: Liebres - España; Carreteras - Impacto medioambiental; game species endemic; incidence of roadkill; Iberian hare–vehicle accidents; hunting quotas; road ecology; demographic compensation; roadkill mitigation